A retrospective study (2009-2018) on the outcome of uncomplicated twin pregnancies in Hospital Sultan Ismail Johor Bahru : the association between gestational age at delivery and the neonatal outcomes - Nor, Nurliza Md (2020)
Introduction: The incidence of twin pregnancy is increasing worldwide1, and so does in Malaysia. It is associated with a higher risk of morbidity and mortality throughout pregnancy to both mother and fetus. This study aims to determine the maternal and fetal characteristic of twin pregnancies in Hospital Sultan Ismail Johor Bahru (HSIJB) and to observe the association between the gestational age at delivery and the delivery outcomes in uncomplicated twin pregnancies. Methodology: This is a retrospective observational study of women with uncomplicated monochorionic and dichorionic twin pregnancies delivered at 36 completed weeks or beyond from January 2009 until December 2018 in HSIJB. The data is divided into 36 weeks group, 37 weeks group, and ≥38 weeks group. The maternal demographic and pregnancy characteristics were observed. The primary outcome was neonatal composite morbidity, which was defined as having one or more of the following: neonatal intensive care unit's admission, low Apgar score, the requirement of mechanical ventilator support, respiratory distress syndrome, and stillbirth or perinatal/ neonatal mortality. The optimal gestational age for delivery according to chorionicity is determine based on the neonatal composite morbidity. Results: A total of 949 sets of twins delivered at HSIJB over ten years, from which 360 women with uncomplicated twin pregnancies and 720 neonatal outcomes were eligible for the study (144 DCDA and 216 MCDA). In DCDA twins, the composite morbidity was least in the 37 weeks group, followed by the ≥ 38 weeks group and then 36 weeks group. On the contrary, more composite morbidity wasseen in the MCDA twinning group at 36 weeks group, followed by the 37 weeks group and later in ≥ 38 weeks group. However, the association between the gestational age at delivery with composite morbidity in MCDA twin were insignificant. Conclusion: Our data suggest that the optimal gestational age for delivery in uncomplicated DCDA twins was at 37 weeks and MCDA twins at ≥38 weeks.